2016
DOI: 10.2217/rme-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapies: The Challenge of sUper-High-Cost Treatments and How to Pay for them

Abstract: Gene therapies have the potential to cure rare conditions that often have no current efficacious treatments with a one-time treatment episode, relieving substantial unmet need and having profound positive impact on patients' lives. However, with the first gene therapy now licensed and priced at around US$1 million per patient, cost and uncertain funding mechanisms present a potential barrier to patient access. In this article, we discuss the unique challenges presented by gene therapies, particularly concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…This increase in approvals, combined with high per patient prices, has led to worries amongst policy makers about the affordability of aggregate OMP expenditure [3, 5, 6]. More recently, the introduction of high-priced gene and cell therapies – many of which are also OMPs – has further focused attention on OMP expenditure [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…This increase in approvals, combined with high per patient prices, has led to worries amongst policy makers about the affordability of aggregate OMP expenditure [3, 5, 6]. More recently, the introduction of high-priced gene and cell therapies – many of which are also OMPs – has further focused attention on OMP expenditure [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…However, we maintain that some kinds of RMPs raise specific challenges, such as gene therapies when they are curative [37]. We have shown that risk-sharing specifically is far less discussed than reimbursement generally.…”
Section: ) Discussionmentioning
confidence: 85%
“…A major drawback of pay-for-outcome schemes is the added burden to both the patient and the healthcare system to monitor the performance of the therapy. These costs can become so high that they outweigh any savings made by such a scheme [3,5,28,49,54,59,64]. The enforcement of additional studies to resolve the uncertainties regarding long-term effects could sometimes also be achieved by implementing a form of coverage with evidence development where it is agreed that the price will drop iteratively by a certain percentage or amount after predefined periods when the manufacturer does not produce the necessary evidence [89].…”
Section: Methodsmentioning
confidence: 99%